Lean production and its application assessment using Set Pair Analysis - Zhan-wen Niu; Bin Zuo; Wei-hong Li (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
Lean production is regarded as the third production paradigm, succeed craft-ship production and mass production. Companies will better adapt to the competitive market by Lean, which is characterized by multi-varieties and small-batch, through continuous improvement and waste elimination, so it is being widely studied and applied. But the absence of universal definition to lean production has hampered its smooth development in China, for non-united definitions making it hard to have a comprehensive and correct image to lean production. Meanwhile, there is rarely research on appraising lean production. Without reasonable assessment tool, companies can not know its application degree of lean production compared with industry leaders, which will impede its continuous improvements. Pointed to this situation, this paper puts forward one reasonable improved definition to lean production based on related references, and then applies Set Pair Analysis to assess leanness degree. Finally a case is given to show this model's feasibility.